Certain peculiarities of the professional pedagogical trend among teachers - Navaitienė, J. (Psichologija, 1988)
The main purpose of the present paper is to reveal some peculiarities of such an important component in the structure of the teacher’s personality as its professional-pedagogical trend and to prove the necessity of special directing measures. The experimental study with different methodics on the basis of S. Kregždė’s instrumental, theory of professional interests was conducted.